Risk factors for positive post-transplantation measurable residual disease in patients with acute lymphoblastic leukemia - Yuewen Wang; Guomei Fu; Lanping Xu; Yu Wang; Yifei Cheng; Yuanyuan Zhang; Xiaohui Zhang; Yanrong Liu; Kaiyan Liu; Xiaojun Huang; Yingjun Chang; Sihan Zhou; et al. (Chinese Medical Journal)
Abstract. Background:. The level of measurable residual disease (MRD) before and after transplantation is related to inferior transplant outcomes, and post-hematopoietic stem cell transplantation measurable residual disease (post-HSCT MRD) has higher prognostic value in determining risk than pre-hematopoietic stem cell transplantation measurable residual disease (pre-HSCT MRD). However, only a few work has been devoted to the risk factors for positive post-HSCT MRD in patients with acute lymphoblastic leukemia (ALL). This study evaluated the risk factors for post-HSCT MRD positivity in patients with ALL who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods:. A total of 1683 ALL patients from Peking University People’s Hospital between January 2009 and December 2019 were enrolled to evaluate the cumulative incidence of post-HSCT MRD. Cox proportional hazard regression models were built for time-to-event outcomes. Multivariable analysis was performed to determine independent influencing factors from the univariable analysis. Results:. Both in total patients and in T-cell ALL or B-cell ALL, pediatric or adult, human leukocyte antigen-matched sibling donor transplantation or haploidentical SCT subgroups, positive pre-HSCT MRD was a risk factor for post-HSCT MRD positivity (P <0.001 for all). Disease status (complete remission 1 [CR1] vs. ≥CR2) was also a risk factor for post-HSCT MRD positivity in all patients and in the B cell-ALL, pediatric, or haploidentical SCT subgroups (P = 0.027; P = 0.003; P = 0.035; P = 0.003, respectively). A risk score for post-HSCT MRD positivity was developed using the variables pre-HSCT MRD and disease status. The cumulative incidence of post-HSCT MRD positivity was 12.3%, 25.1%, and 38.8% for subjects with scores of 0, 1, and 2–3, respectively (P <0.001). Multivariable analysis confirmed the association of the risk score with the cumulative incidence of post-HSCT MRD positivity and relapse as well as leukemia-free survival and overall survival. Conclusion:. Our results indicated that positive pre-MRD and disease status were two independent risk factors for post-HSCT MRD positivity in patients with ALL who underwent allo-HSCT.